Irkutsk Region Governor’s Prize 2024 awarded to architects - Lisitsina, Yana; Lisitsin, Vasily (project baikal, 2025)
In 2024, The Irkutsk Region Governor’s Prize, which is given to artists for their achievements in the field of culture and art in the nomination “Works of architecture, urban planning and landscape art”, was awarded to a creative team consisting of A. V. Doroshenko, V. A. Kitaev, O. B. Badula, A. G. Petunin and A. O. Kuzmicheva. The article gives information about the laureates of the prize.
Keywords: Irkutsk Region Governor’s Prize 2024; Irkutsk; architecture; A. V. Doroshenko, V. A. Kitaev, O. B. Badula, A. G. Petunin, A. O. Kuzmicheva